INTRACTABLE HEMATURIA IN BLADDER CANCER WITH UNILATERAL HIGH GRADE VESICOURETERAL REFLUX: A CONSERVATIVE APPROACH USING INTRAVESICAL FORMALDEHYDE INSTILLATION - Rustandi, Reginald; Santoso, Rachmat Budi; Harahap, Edward Usfi; Bramono, Ikhlas Arief (Indonesian Urological Association, 2025)
Objective: This study aims to report a case of intractable hematuria in a patient with bladder cancer after radiotherapy. Case(s) Presentation: This case reported a 41-year-old male with urothelial carcinoma of bladder who came to our hospital hematuria symptoms that arised four months after radiotherapy session. The patient was admitted several times with intractable hematuria along with low levels of hemoglobin, and diagnosed with cystitis radiation. Discussion: Voiding cystourethrogram (VCUG) showed unilateral high grade vesicoureteral reflux (VUR). The patient showed no sign of improvement after transarterial embolization (TAE), radiation, and high-dose of steroids. However, the symptoms finally resoluted after formaldehyde instillation. Conclusion: Patients with a history of bladder cancer who develop hematuria after radiotherapy should be evaluated promptly to exclude the possibility of recurrent disease. The administration of formaldehyde instillation could lower the symptoms of hematuria and maintain hemoglobin levels. Keywords: Intractabel hematuria, formaldehyde, bladder cancer.